Finite-time quantum heat engines. - Molitor, Otavio Augusto Dantas (2020)
In the last decade, the study of thermodynamic phenomena in ultra-small scales, where quantum mechanics becomes imperative, has gained a lot of attention. The possibility of controlling single quantum states in nowadays experimental setups has encouraged a more intense inquiry over the intersection between thermodynamics and quantum mechanics, which is known as quantum thermodynamics. Particularly relevant in this framework is the study of quantum heat engines, that is, quantum systems undergoing thermodynamic cycles. Thermodynamic cycles contain all the aspects of thermodynamics, thus its a good testbed for a better comprehension of the thermodynamics of quantum systems. Moreover, modelling quantum heat engines is crucial for the design of future ultra-small engines. Nonetheless, another aspect must be taken into account, finite-time operation. Its very important for the optimization of the output power of the engine. In this dissertation, we present a new model of finite-time quantum heat engines. By making use of collisional models, we construct a model in which a generic quantum chain experiences sequential pure heat and pure work strokes. Dictated by stroboscopic evolution, the engines state goes through a transient regime until the limit-cycle is reached. After the achievement of the limit-cycle, our results indicate that only the boundary sites of the quantum chain are relevant for the heat currents exchanged with the baths. By means of analytical and numerical methods, we present how the model is useful for optimizing the output power of stroke-based quantum heat engines, without decreasing their respective efficiencies. Lastly, we prove that there is a universal efficiency value, the Otto efficiency, for a whole family of models containing a specific kind of internal interactions. For completeness, other methods from the literature which deal with finite-time quantum heat engines are also presented and discussed.